2021
DOI: 10.3390/jmse9020187
|View full text |Cite
|
Sign up to set email alerts
|

Marine Environmental Regionalization for the Beibu Gulf Based on a Physical-Biological Model

Abstract: A physical–biological ocean model was employed to investigate characteristics of the Beibu Gulf in the northwest South China Sea (SCS) from 2011 to 2015. We adopted the spatially constrained multivariate clustering method to determine the refined marine environmental regionalization using 10 variables from the model output, and compared regionalization differences in ENSO (El Niño–Southern Oscillation) years. The simulated physical and biochemical variables display a wide spectrum of patterns in space and time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…After RDA, the dissolved oxygen level in the research area was negatively correlated with DIN content, which was consistent with the research results in the same area [25]. The spatial distribution of DO is also consistent with the distribution of multiyear averages [30], although different seasons will cause significant differences in the average level of dissolved oxygen, but overall, it presents a trend of higher in the north and lower in the south. COD has a higher concentration in coastal areas, which is likely to be closely related to human activities on both sides of the research area, such as a large amount of aquaculture in Xuwen County along the coast and many residential areas distributed in Haikou City on the south side.…”
Section: Hydrodynamic Factors and Artificial Activities Impacting Wat...supporting
confidence: 87%
“…After RDA, the dissolved oxygen level in the research area was negatively correlated with DIN content, which was consistent with the research results in the same area [25]. The spatial distribution of DO is also consistent with the distribution of multiyear averages [30], although different seasons will cause significant differences in the average level of dissolved oxygen, but overall, it presents a trend of higher in the north and lower in the south. COD has a higher concentration in coastal areas, which is likely to be closely related to human activities on both sides of the research area, such as a large amount of aquaculture in Xuwen County along the coast and many residential areas distributed in Haikou City on the south side.…”
Section: Hydrodynamic Factors and Artificial Activities Impacting Wat...supporting
confidence: 87%
“…Previous studies suggested that monsoon wind is the primary driving factor of winter circulation in the BG (Gao et al., 2017; Xia et al., 2001), which could retain the nutrients input from SCSW and WGCC in the central gulf under the effects of strong northeastern monsoon during the winter. In the late winter and early spring, with the weakening of the northeastern monsoon and hydrodynamic conditions, and the gradual increase of temperature, abundant nutrients supplied by the WGCC and SCSW (most from WGCC) are conducive to the growth of phytoplankton in the central BG, and thus phytoplankton blooms (He et al., 2019; Pan et al., 2021; Shen et al., 2018; Xu et al., 2019). Thus, the abundant nutrients supplied from WGCC and SCSW may be responsible for the frequent phytoplankton blooms in the central BG during the late winter.…”
Section: Discussionmentioning
confidence: 99%